Perspectives on Systems Modeling of Human Peripheral Blood Mononuclear Cells - Sen, Partho; Kemppainen, Esko; Orešič, Matej (Frontiers in Molecular Biosciences, 2018)
Human peripheral blood mononuclear cells (PBMCs) are the key drivers of the immune responses. These cells undergo activation, proliferation and differentiation into various subsets. During these processes they initiate metabolic reprogramming, which is coordinated by specific gene and protein activities. PBMCs as a model system have been widely used to study metabolic and autoimmune diseases. Herein we review various omics and systems-based approaches such as transcriptomics, epigenomics, proteomics and metabolomics as applied to PBMCs, particularly T helper subsets, that unveiled disease markers and the underlying mechanisms. We also discuss and emphasize several aspects of T cell metabolic modelling in healthy and disease states using genome-scale metabolic models.